Peningkatan Kesadaran Anti-Bullying di SDN 1 dan 2 Ciherang: Program Sosialisasi untuk Anak Kelas 5 - Khansa, Nabilla; Farisya, Dhita Shaleh; Rahman, Faisal Fajri; Rama, Nadi; Lutpiani, Anisa; Sari, Sindi Fatikah; Wachdijono, Wachdijono; Marwah, Suci (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Anti-bullying socialization activities at SDN 1 and 2 Ciherang were carried out as part of the Real Work Lecture (KKN) program with the aim of increasing students' awareness of the negative impacts of bullying. This program involved interactive methods, such as games and simulations, to facilitate students' understanding of various forms of bullying and how to prevent them. In addition, this program also involved parents and teachers, as well as cooperation with the local police to create a holistic approach. The evaluation showed an increase in students' understanding by 60% after the activity. These results support the effectiveness of educational interventions in reducing bullying cases in schools and emphasize the need for effective reporting mechanisms. This program is expected to be a model for similar efforts in other schools to create a safe and inclusive learning environment.